Biologia reprodutiva de Hypsiboas lundii (Anura, Hylidae) em um fragmento de Cerrado no sudoeste de Minas Gerais - Mazzarelli, Cilene Cristina Mathias [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Currently, approximately 7390 amphibian species are known in the world, with a great diversity in Brazil: 1026 amphibians, of which 988 are anuran species. Distribution and reproduction of species are greatly influenced by local climatic conditions. In the seasonal tropics, species exhibit a temporal reproductive pattern more associated to the rainy season, while in more stable regions, such as tropical rain forests, reproduction is more influenced by the temperature. Anuran species adopt a variety of strategies to maximize reproductive success, which are related to the temporal reproductive pattern. Explosive species reproduce in a short period of time, and competition among males is more intense compared to prolonged breeding species. Moreover, anurans commonly change strategies according to social contexts, such as aggressive interactions or courtship, which may involve many stimuli types, such as acoustic, tactile, chemical and visual. The present study was conducted in the Cerrado, a formation composed by many different types of phytophysiognomies, from grassfields to forests. We describe the reproductive biology of the hylid frog Hypsiboas lundii, a species widely distributed throughout the Cerrado with a life cycle associated to streams. Observations were monthly between Oct/2013 and Jan/2015, in the municipality of Sacramento, Minas Gerais state. The species exhibited a prolonged reproductive pattern, with males calling from Oct/2013 to May/2014, and in Dec/2014 and Jan/2015, predominantly from the ground. Courtship behavior was complex, involving acoustic and tactile signals. Clutches were deposited mainly in depressions at the stream banks, which were previously inspected by females and, after amplexus, enhanced by them. Aggressive interactions involved territorial call emission and vocal duels. We also describe advertisement, courtship and territorial calls, which were mainly differentiated by note duration and intensity

Atualmente são descritas aproximadamente 7390 espécies de anfíbios no mundo, com o Brasil detendo uma grande diversidade de espécies: 1026 espécies de anfíbios, das quais 988 são anuros. A distribuição e reprodução das espécies são muito influenciadas pelas condições climáticas locais. Nos trópicos sazonais as espécies apresentam um padrão temporal de reprodução mais associado à estação chuvosa, enquanto que em locais mais estáveis, como florestas chuvosas, a reprodução sofre maior influência da temperatura. Há diversas estratégias adotadas pelas espécies de anuros a fim de maximizar seu sucesso reprodutivo, as quais estão relacionadas com o padrão temporal de reprodução. As espécies consideradas explosivas se reproduzem em um curto espaço de tempo, e a competição entre machos é mais intensa do que quando comparada às espécies de reprodução prolongada. Além disso, é comum os anuros alterarem as estratégias de acordo com o contexto social, como em interações agressivas e de corte, as quais podem envolver muitos tipos de estímulos, tais como acústicos, táteis, químicos e visuais. O presente estudo foi desenvolvido em uma área de Cerrado, uma formação que abrange uma grande diversidade de fitofisionomias, desde campos até matas. Descrevemos aqui a biologia reprodutiva do hilídeo Hypsiboas lundii, uma espécie amplamente distribuída pelo Cerrado, com ciclo de vida restrito à matas de galeria. As observações foram mensais entre out/2013 e jan/2015, no município de Sacramento, Minas Gerais. A espécie apresentou reprodução prolongada, com os machos vocalizando de outubro/2013 a maio/2014, e em dez/2014 e jan/2015, predominantemente sobre o solo. A espécie apresentou comportamento de corte complexo, envolvendo sinais acústicos e táteis. As desovas foram depositadas, principalmente, em depressões às margens de riachos, as quais foram previamente vistoriadas pela fêmea e,...
Keywords: Anura; Anuro - Reprodução; Anuro - Vocalização; Anfíbio; Minas Gerais